2002
DOI: 10.1046/j.1528-1157.2002.45200.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Regulation through Hypothalamic GABAA Receptors in a Genetic Absence Epilepsy Model in Rat

Abstract: Summary:Purpose: ␥-Aminobutyric acid (GABA) plays a vital role in both central cardiovascular homeostasis and pathogenesis of epilepsy. Epilepsy affects autonomic nervous system functions. In this study, we aimed to clarify the role of GABA A receptors in hypothalamic cardiovascular regulation in a genetically determined animal model of absence epilepsy.Methods: Nonepileptic Wistar rats and genetic absence epilepsy rats from Strasbourg (GAERS) were instrumented with a guide cannula for drug injection and extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…injection of 0.3 nmol of bicuculline caused a decrease in the duration of SWDs in the EEG of the GAERS group. This finding is in agreement with the earlier data from this laboratory (11). Likewise, Peeters et al have demonstrated that i.c.v.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…injection of 0.3 nmol of bicuculline caused a decrease in the duration of SWDs in the EEG of the GAERS group. This finding is in agreement with the earlier data from this laboratory (11). Likewise, Peeters et al have demonstrated that i.c.v.…”
Section: Discussionsupporting
confidence: 93%
“…bicuculline were found to be increased in the WAG / Rij rat, which is one of the best characterized genetic rat models of absence epilepsy, where the smallest dose of bicuculline failed to generate a cardiovascular response in non-epileptic Wistar control rats (10). Moreover, the GAERS generate more prominent increases in blood pressure when bicuculline was given into the DMH of GAERS when compared to the non-epileptic control rats (11). We have previously demonstrated that BMI caused dosedependent increases in both blood pressure and heart rate in conscious rats when injected intracerebroventricularly (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best examples utilise GABA, ␥-hydroxy-butyric-acid (GHB) and N-methyl-d-aspartate (NMDA), demonstrating differences in drug induced seizure activity between nuclei (Aker and Onat, 2002;Block, 1994;Hosford et al, 1997a,b;Millan et al, 1986a,b;Snead, 1991). However, very few of these studies have reported the accuracy of the injections, nor the diffusion distances of the injected compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, this represents significant technical challenges as these structures are very small. While there have been few studies that have reported performing microinjections into these and other regions (Aker and Onat, 2002;Hosford et al, 1997a,b;Liu et al, 1991;Millan et al, 1986a,b;Snead, 1991), there has been very little systematic studies validating the accuracy of these injections and how far the drug diffuses away from the injection site into surrounding structures. One epilepsy study measured the spread of a tritium labelled 2-amino-7-phosphoheptanoic acid ([ 3 H] APH) in the prepiriform cortex (Millan et al, 1986b).…”
Section: Introductionmentioning
confidence: 99%